Role of Systematic Formative Assessment on Students’ Views of Their Learning - Areiza Restrepo Hugo Nelson (Profile: Issues in Teachers' Professional Development)
<span style="font-size: 10.0pt; font-family: ";Verdana";,";sans-serif";; mso-fareast-font-family: ";Times New Roman";; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: ES-CO; mso-bidi-language: AR-SA;" lang="EN-US">This article presents a partial report of a small qualitative research study that explored the students’ views of their learning during and after the implementation of formative procedures such as self-assessment, feedback, and conferences. The article also includes their perceptions about this implementation. The research was carried out with a group of students of English enrolled in an extension program of a Colombian public university. The results showed that formative assessment helped these learners to be aware of their communicative competence and to perceive the situations in which they developed this awareness; it also enabled them to experience success in their learning. Also, learners identified the purposes of this kind of assessment and perceived formative assessment as a transparent procedure. <span style="font-size: 10.0pt; font-family: ";Verdana";,";sans-serif";; mso-fareast-font-family: ";Times New Roman";; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: ES-CO; mso-bidi-language: AR-SA;" lang="EN-US">Este artículo presenta el reporte parcial de un pequeño estudio de investigación de tipo cualitativo que exploró las percepciones de los estudiantes sobre su aprendizaje durante y después de la implementación de una evaluación formativa sistemática y sus visiones sobre este tipo de intervención. El estudio se llevó a cabo en un grupo de estudiantes de inglés pertenecientes a un programa de extensión de enseñanza de lenguas extranjeras en una universidad pública colombiana. Los resultados mostraron que la evaluación formativa ayudó a estos estudiantes a ser conscientes de su competencia comunicativa y a reconocer las situaciones en las que se generó tal conciencia; además, también les permitió experimentar éxito en su aprendizaje. Asimismo, los estudiantes identificaron los propósitos de este tipo de evaluación, la cual percibieron como un proceso transparente.